Stakeholder Agility As An Enabler of Strategy Implementation: Evidence from the Zimbabwe Public Tertiary Education Institutions - Matshe, Nancy (Acta Universitatis Danubius. Œconomica, 2023)
The full value of any strategic objective is achieved through effective strategy implementation. However, globally, strategy implementation is arguably the most significant drawback of the strategic management process, with failure rates as high as 90%. This article is aimed at determining the extent to which stakeholder agility contributes to successful strategy implementation in public tertiary education institutions in Zimbabwe, so that, they may contribute meaningfully to the socio-economic development of the nation. The study was motivated by the lack of prior research on the nexus between stakeholder engagement and strategy implementation in public education. Data was analysed from 486 questionnaires that were randomly distributed to the senior management of tertiary education institutions. Correlations, and regression analyses techniques were used to determine the extent to which stakeholder agility predicts strategy implementation. The results indicated that external stakeholder agility positively influences successful strategy implementation, whilst internal stakeholder agility does not. The study provides guidance to tertiary education institutions on enhancing strategy implementation through external stakeholder agility. This paper also provides evidence in the African context on the reduction of the strategy implementation failure through stakeholder agility practices relevant to the public education sector.